KNOWLEDGE, ATTITUDES, AND PRACTICES TOWARD CORONAVIRUS DISEASE-19 INFECTION AMONG RESIDENTS OF DELHI NCR, INDIA: A CROSS-SECTIONAL SURVEY BASED STUDY - AQEEL, UBADA; DAUD ALI, MOHAMMAD; IQBAL, ZEENAT; MIRZA, MOHD. AAMIR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: In the given study, we have carried out a survey among general population of Delhi NCR (India) for the knowledge, perceptions, and attitude toward coronavirus disease (COVID-19) and also attempted to reach to a few conclusions in the form of recommendations. Methods: A cross-sectional questionnaire based online survey (using Google Forms) was conducted between April 2020 and May 2020 to investigative knowledge, perceptions, and attitude toward COVID-19. Chi-square test was used for the computation of p-value. Results: There were total 823 respondents, with 43.01% females and 56.98% males. Around 73.74% respondents believe that it has become a social stigma. About 75.09% were of the opinion that sneezing etiquettes can help in curbing the infection. About 93.43% of study population follows the personal hygiene, 24.78% wished to get insurance coverage. Similarly, interesting data were collected over different aspects of COVID-19. Conclusions: The current pandemic is the first exposure at such a large scale to the existing population but with the progression of time, authorities and general population are collating knowledge about the same. It is to be fought at all the fronts such as medical, social, economic, and psychological. Hence, this type of survey becomes an important tool in decision making.